First record of two hard coral species (Faviidae and Siderastreidae) from Qeshm Island (Persian Gulf, Iran) - MAHDI MORADI; EHSAN KAMRANI; MOHAMMAD R. SHOKRI; MOHAMMAD SHARIF RANJBAR; MAJID ASKARI HESNI (Smujo International, 2010)
Abstract. Moradi M, Kamrani E, Shokri MR, Ranjbar MS, Hesni MA (2009) First record of two hard coral species (Faviidae and Siderastreidae) from Qeshm Island (Persian Gulf, Iran). Nusantara Bioscience 2: 34-37. Two species of hard corals including Cyphastrea chalcidicum (Forskal 1775) (Faviidae) and Coscinaraea monile (Forskal 1775) (Siderastreidae) were collected from the south of Qeshm Island (Persian Gulf, Iran) in the late of 2008. These species were previously reported from southern Persian Gulf, Gulf of Aden, Southeast Africa, and Indo-Pacific. The literature review on the distribution of these two species revealed that these species were firstly recorded from the Persian Gulf. These findings further emphasize the high diversity of coral fauna in the Iranian waters of the northern Persian Gulf.